Abu Abdullah Muhammad bin Ibrahim Al-Bushangi (T.: 290 AH / 902 AD) and his hadith efforts - Al-Moussawi, Warood Nori Hussein (Linguistics and Culture Review, 2021)
Modern industry has great importance in the literature of hadith sciences, hadith scholars paid special attention to the hadith of the Prophet because of its sanctity linked to human belief, as well as the slander of lying against the Messenger of God (may God bless him and grant him peace). And they were interested in the methods of his narration, because among the basics of accepting the hadith is the methods of its transmission, and one of the scholars who have a long history in this field is Abu Abdullah Al-Bushinji, who died in the year 290 AH / 902 AD. The focus of attention and attention of scholars and narrators of hadith.